Awareness and Knowledge Regarding the Concept of Shortened Dental Arches Among Dental Surgeons in Karachi, Pakistan: Awareness of Shortened Dental Arches - Kumar, Kelash; Tariq, .; Ambreen, .; Saqib, .; Iqbal, Uzma Anam; Mushtaque, Saher (Pakistan Journal of Health Sciences, 2024)
Tooth loss remains a major oral health problem with a high public and individual health effect. impacting the majority of persons in their middle and older years. Objective: To evaluate knowledge and comprehension of the idea of shortened dental arches among dental surgeons of Karachi, Pakistan. Methods: A convenience sample of 300 dentists who work in private hospitals in Karachi was used to perform a descriptive cross-sectional survey. A self-administered questionnaire was given to the participants to ask opinions regarding awareness, function, aesthetics, and comfort of the shortened dental arch concept. SPSS version 25.0 was used to statistically analyze the data from June 2023 to December 2023. Results: The results of the study revealed that approximately 31.7% believed that shortened dental arches offer a generally good periodontal prognosis, 33.8% of dental surgeons revealed that few restorative treatments were available, 31.2% believed that shortened dental arches do not lower the risk of overtreatment, 32.66% prolong the retention of natural teeth, 30% decrease the occlusal vertical dimension and 32.4% had TMJ issues. Conclusions: Dental surgeons’ attitudes and comprehension of the shortened dental arches concept were inadequate. Hence shortened dental arches provide a practical approach to dental care by preserving posterior tooth function without requiring complete arch restoration. By improving clinical decision-making, it was possible to improve patient outcomes by having a better understanding of the existing level of awareness and expertise among dental surgeons.